Distinct Subdivisions in the Transition Between Telencephalon and Hypothalamus Produce Otp and Sim1 Cells for the Extended Amygdala in Sauropsids - Metwalli, Alek H.; Abellán, Antonio; Freixes, Júlia; Pross, Alessandra; Desfilis, Ester; Medina, Loreta (Frontiers in Neuroanatomy, 2022)
Based on the coexpression of the transcription factors Foxg1 and Otp, we recently identified in the mouse a new radial embryonic division named the telencephalon-opto-hypothalamic (TOH) domain that produces the vast majority of glutamatergic neurons found in the medial extended amygdala. To know whether a similar division exists in other amniotes, we carried out double labeling of Foxg1 and Otp in embryonic brain sections of two species of sauropsids, the domestic chicken (Gallus gallus domesticus), and the long-tailed lacertid lizard (Psammodromus algirus). Since in mice Otp overlaps with the transcription factor Sim1, we also analyzed the coexpression of Foxg1 and Sim1 and compared it to the glutamatergic cell marker VGLUT2. Our results showed that the TOH domain is also present in sauropsids and produces subpopulations of Otp/Foxg1 and Sim1/Foxg1 cells for the medial extended amygdala. In addition, we found Sim1/Foxg1 cells that invade the central extended amygdala, and other Otp and Sim1 cells not coexpressing Foxg1 that invade the extended and the pallial amygdala. These different Otp and Sim1 cell subpopulations, with or without Foxg1, are likely glutamatergic. Our results highlight the complex divisional organization of telencephalon-hypothalamic transition, which contributes to the heterogeneity of amygdalar cells. In addition, our results open new venues to study further the amygdalar cells derived from different divisions around this transition zone and their relationship to other cells derived from the pallium or the subpallium.